Making the Arctic predictable: the changing information infrastructure of Arctic weather and sea ice services. (2nd October 2018) - Knol, Maaike; Arbo, Peter; Duske, Paula; Gerland, Sebastian; Lamers, Machiel; Pavlova, Olga; Sivle, Anders Doksæter; Tronstad, Stein
ABSTRACT: This paper explores the changing infrastructure around weather and sea ice information provisioning for Arctic marine areas. Traditionally, the most important providers of operational information on sea ice and weather conditions are the national sea ice and meteorological services. More recently, the community of Arctic information providers has become more heterogeneous with the establishment of numerous collaborative platforms. Three case studies will enhance our understanding of current developments (BarentsWatch, Polar View and Arctic Web). We analyze their organization and funding structures, the types of services they develop, and their target groups. Based upon these cases, we discuss the information infrastructure's dynamics and underlying drivers of change. Apart from an expected need for customized services due to changing Arctic activity patterns, new initiatives arise due to a combination of (1) progress in information and communication technology, (2) a need to enhance interoperability of data systems, (3) and a desire to improve customized data conveyance from provider to user. The paper concludes with a discussion of the implications of the changing Arctic information infrastructure and defines directions for further research.